Congenital Bronchobiliary Fistula: A Case Report and Literature Review - Bing, Zhen; Chen, Rui; Xing, Pengchao; Ren, Yueyi; Hou, Kefeng (Frontiers in Pediatrics, 2021)
Congenital bronchobiliary fistula (CBBF) is a rare disease. Children with CBBF mostly have atypical clinical manifestations and easy to be missed. We report a case of a child with CBBF who was diagnosed with fistulography with the help of an endobronchial blocker and fiberoptic bronchoscope. The CBBF was successfully removed by thoracoscopic surgery.